Analysis of the Relationship of Inertia and Net Load in the Chilean Power System - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2022)
The Chilean power system is dominated by thermal and hydraulic units that make it a robust system in inertia. In recent times there has been an increase in renewable generation units in the system, which do not have inertia. In addition, decarbonization policies propose the replacement of thermal units with renewable ones. Therefore, the Chilean power system will be a low inertia system in the future, so the improvement of techniques to identify inertia will be of great importance. This work shows the use of Unit Commitment and Data Driven techniques to identify the inertia of the Chilean power system, comparing them with each other and with other electrical systems. © 2022 IEEE.